'Co-creating meeting spaces': Feminist ethnographic fieldwork in Bangladesh. Issue 6 (2nd June 2020) - Williams, Shoshannah; Drew, Georgina
Abstract: The effort to work with stigmatized and socially vulnerable women holds particular challenges for feminist researchers attempting to engage in critical and reflexive fieldwork. Primarily drawing from ethnographic research with women experiencing homelessness within a train station in Dhaka, Bangladesh, this paper explores the particular challenges of engaging with women whose lives have been shaped by shame, stigma and violence—and who are understandably distrustful of outsiders asking questions. It presents some of the finer interpersonal measures and considerations for respectfully and sensitively working with such 'hard to reach' women where the potential for 'insider' research is limited. Building upon fieldwork insights, we advance the importance of fostering 'co-creating meeting spaces'. This terminology flags the shared process between researchers and interlocutors to co-create the physical and emotional spaces that enable conversations, based on trust and mutual respect, to occur. As an approach, rather than a prescriptive set of fieldwork methods, the act of co-creating meeting spaces encourages researchers engaged in prolonged fieldwork to lean into the surprising moments of encounter, sharing, and tentative alliances that emerge and are created between researchers and interlocutors who hold distinct but equally significant power dynamics in the research endeavor. The approach offers a means of grappling with the messy, difficult, and slow process of navigating and (re)negotiating the physical and emotional spaces that are apt to emerge when working with women whose everyday resilience in the face of adversity is based upon their self-reliance and guardedness against unreliable others.